Peran Orang Muda Katolik dalam Upaya Moderasi Umat Beragama Melalui Media Sosial - Marini Marini; Intansakti Pius X (Jurnal Silih Asuh : Teologi dan Misi, 2024)
In the digital era, social media has become an important platform for communication and interaction, including in terms of religion. Young Catholics play an important role in religious moderation through social media. This study explores this role, focusing on the results and discussions, observations, social media content and challenges faced. Young Catholics actively use social media to interact about religion, share information, and promote moderation, young Catholics face challenges such as hate speech, misinformation and Cyberbullying, the Catholic Church can play an important role in supporting the role of young Catholics in religious moderation through social media. This type of research uses a Qualitative method by collecting and analyzing data obtained from various sources such as articles, books and Church documents. In this study, researchers rely on various literature and do not interact directly with research subjects. And also by analyzing the content posted by young Catholics on social media to identify themes, trends, and patterns related to religious moderation, analyzing online interactions between young Catholics from different religions and cultures to understand how they navigate differences and promote interfaith dialogue, analyzing how mainstream media and social media platforms cover the role of young Catholics in religious moderation. The findings of this researcher show that the role of young Catholics has the potential to play an important role in religious moderation through social media. However, they also face challenges in using social media effectively for this purpose, namely: Hate speech and Negative Content, Misinformation and Propaganda, Cyberbullying and Online Harassment, Lack of Digital Literacy, Lack of support and guidance.